PENGARUH SUHU DAN LAMA PENGERINGAN TERHADAP SIFAT KIMIA DANORGANOLEPTIK TEPUNG UMBI TALAS (Colocasia esculenta) - Erni, Nurfiani; Kadirman, Kadirman; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2018)
This study aims at knowing the influence of temperature and leght of drying to chemical characteristic and organoleptic of taro flour. This study is an experimental study using complete random design, factorial pattern which is consisted of two factors namely: drying temperature (P1 = 50 0C, and P2= 60 0C) and length of drying (T1 = 8 hours, and T2 = 10 hours) with three time repetition. Variables observed were rendamen, the content of water, the content of ashes, the content of protein, the content of carbohydrate, the appearance, the smell and texture. Analysis technic used ini this study were analysis of variance (ANOVA) and Duncan advanced test which were calculated through software statistical package for social science (SPSS) version 21.0. The results showed that temperature and length of drying had an evident influence to the chemical characteristic and organoleptic of taro flour. The results of the chemical characteristic and organoleptic of taro flour covered 8,57 % rendamen, 11,80 % water, 11,46 % ashes, 5,95 % protein, 73,58 % carbohydrate, 8,60 % in appearance, 6,82 % in smell, and 7,20 % in texture